Caracterização da matéria orgânica, atributos químicos e físicos do solo sob diferentes sistemas de manejo na região Oeste do Paraná - Rosset, Jean Sérgio (2015)
The evaluation of the quality of agricultural production systems is of great importance for the maintenance and increase of production capacity of agricultural areas. Soil organic matter (SOM) and their fractions, associated with other indicators, provides satisfactory results for the assessment of soil properties. The aims of this study were to determine the effects of management systems with different deployment times on soil chemical and physical properties, total soil organic carbon (TOC) stock and its indicators; to assess the distribution and stock of soil organic matter fractions; and to assess the carbon management index (CMI), soil structural quality indicators based on particle size and aggregate stability and evolution of carbon in the form of carbon dioxide (CO2) into aggregates incubated in the laboratory. Soil samples were collected in agricultural systems located in Guaíra, Paraná State, Brazil. Five managed areas and a reference area (native forest) without anthropic action were analyzed in a completely randomized design with five replications. Management systems include three areas with different time of first adoption of the no-till: 6 (NT6), 14 (NT14) and 22 years (NT22) under continuous soybean maize or wheat cropping system; 12 years of no-till under soybean maize or wheat cropping systems, and in the last four years with integration of maize and ruzigrass (Brachiaria ruziziensis) (NT+B) and an area of permanent and continuous extensive cattle pasture of coast-cross (Cynodon dactylon). Soil physical and chemical properties, TOC stock and distribution and stock of soil organic matter fractions were evaluated at depths from 0-0.05; 0.05-0.1; 0.1-0.2 and 0.2-0.4 m. Soil aggregate stability was evaluated at depths from 0-0.05 and 0.05-0.1 m. The managed areas showed the lowest values for total soil porosity, and higher values for soil bulk density and soil penetration resistance for area compared to the native forest area. There was slow and gradual increase in the TOC stocks due to the time of adoption of the no-till practices, with significant differences in the area with 22 years of no-tillage compared with other areas. There was increase of carbon in the deep layers of soil by the action of the root system of grasses. There was predominance of humin fraction (H) in relation fractions of the alkaline extract (AE), humic acid (HA) and fulvic acid (FA), with percolation of AE fractions in depth. The oxidizable fractions of soil organic matter showed a balance in their relative distribution, and continuous soybean, maize/wheat cropping system contributed to the increase of labile carbon fraction, especially F1. The NT22 area showed the best CMI indicators compared to other managed areas. The time of adoption of the NT improved the structural parameters of soil aggregation and biological activity through the evolution of CO2. The M+B consortium promoted improvements in the structural quality of soil aggregates. The best soil quality indicators among the managed areas were obtained after 22 years of no-till adoption, indicating the improvement of soil quality with the time of adoption of this conservation management system